Calcium‐binding proteins in focal cortical dysplasia. (17th June 2015) - Kuchukhidze, Giorgi; Wieselthaler‐Hölzl, Anna; Drexel, Meinrad; Unterberger, Iris; Luef, Gerhard; Ortler, Martin; Becker, Albert J.; Trinka, Eugen; Sperk, Günther
Summary Objective Alterations in γ‐aminobutyric acid (GABA)‐ergic cortical neurons have been reported in focal cortical dysplasia (FCD)Ia/IIIa, a malformation of cortical development associated with drug‐resistant epilepsy. We compared numbers of neurons containing calcium‐binding proteins parvalbumin (PV), calbindin (CB), and calretinin (CR) and densities of respective fibers in lateral temporal lobe surgical specimens of 17 patients with FCD with 19 patients who underwent anterior temporal lobe resection due to nonlesional temporal lobe epilepsy (non‐FCD) as well as with 7 postmortem controls. Methods PV‐, CB‐, and CR‐immunoreactive (IR) neurons were quantitatively investigated with use of two‐dimensional cell counting and densitometry (reflecting mainly IR fibers) in cortical layers II, IV, and V. Results Numbers of PV‐IR neurons, ratios of PV‐containing to Nissl‐stained neurons (correcting for eventual cell loss), and densities of PV‐IR were higher in layer II of the cortex of FCD compared to non‐FCD patients. Similarly, densities of CB‐IR and CR‐IR were also higher in layers II and V, respectively, of FCD than of non‐FCD patients. Comparison with postmortem controls revealed significant higher cell numbers and fiber labeling for all three calcium‐binding proteins in FCD cortex, whereas numbers of Nissl‐stained neurons did not vary between FCD, non‐FCD, and postmortem controls. In non‐FCD versus postmortem controls, ratios of calcium‐binding protein‐IR cells to Nissl‐stained neurons were unchanged in most instances except for increased CB/Nissl ratios and CB‐IR densities in all cortical layers. Significance Increased numbers of PV neurons and fiber labeling in FCD compared to nondysplastic epileptic temporal neocortex and postmortem controls may be related to cortical malformation, whereas an increased number of CB‐IR neurons and fiber labeling both in FCD and non‐FCD specimens compared with postmortem controls may be associated with ongoing seizure activity. The observed changes may represent increased expression of calcium‐binding proteins and thus compensatory mechanisms for seizures and neuronal loss in drug‐resistant epilepsy.